Risk According to the Relational Theory of Society - Mangone, Emiliana (Stan Rzeczy, 2017)
Taking social relations into consideration allows us to be mindful of the life-world and the social system. A social relation should be intended as an emergent phenomenon of a mutual act, with an autonomous connotation that goes beyond those who implement it. At the same time, it can be traced back to referential semantics, as it exists within a framework of symbolic meaning, and to structural semantics, because it is at the same time a resource and a constraint for the social system. If these are the general foundations of the relational theory of society, adding risk to this perspective as a descriptive model has some distinguishing features. For example, as a dimension of everyday life it is a “neutral category.” It is based on that “insecure security” whose results, positive or negative, will derive from the kind of balance established between “resources and challenges” or, as we claim in this paper, between “goals and means.”